Photosynthetic characters in relation to yield of cucumber grown in naturally ventilated poly house - Rajasekharan, Gayathri; Nandini, K. (Journal of Tropical Agriculture, 2016)
The main principle of poly house cultivation is the facilitation of favourable micro-climate, which favours maximum production. The UV-stabilized plastic sheet which covers the top of the poly house selectively screens the various spectral components of solar radiation and transforms direct sunlight into scattered light. Optimal photosynthesis of leaves involves the harmonious relationship between spectral management and the resultant PAR in poly house. Hence, basic information on the physiological aspects involved in the photoresponse of crop in poly house is needed to realize maximum yield potential. In this context, a study was undertaken to compare the photosynthetic productivity of gynoecious parthenocarpic cucumber which is widely grown in naturally ventilated poly house with that in open conditions. The study revealed that the low intercellular CO2 concentration and high stomatal resistance caused low carboxylation efficiency and photosynthetic rate at early stages of growth in poly house compared to open condition. But at later stages of growth, the carboxylation efficiency and photosynthetic rate was maintained even 60 DAS due to lower rate of stomatal limitations. This facilitates prolonged harvest and more number of harvests from poly house crop. The Fv/Fm ratio, which expresses the maximum photochemical efficiency of PS II, was lower under open condition compared to poly house.